Plant secretions prevent wasp parasitism in nests of wool-carder bees, with implications for the diversification of nesting materials in Megachilidae - Eltz, Thomas; Küttner, Jennifer; Lunau, Klaus; Tollrian, Ralph (Frontiers in Ecology and Evolution, 2015)
Bees make use of plant substrates in more ways than any other group of insects, which is probably linked to their diversification and ecological success. The highly diverse Megachilidae use a wide range of plant-derived brood cell-building materials, including plant leaves, mortar made from plant tissue, resin, plant hairs (“plant wool”), and plant trichome secretions. While certain plant-derived materials are believed to protect nests against microbial decay, this has not been tested, and the factors driving diversification of nesting materials are poorly understood. Here, we investigated the protective effects of plant-derived extrafloral trichome secretions which female European wool-carder bees, Anthidium manicatum, smear on their brood cells. By breeding bees in cages with differential resource supply we generated brood cells with or without trichome secretions. Brood cells with trichome secretions were less attractive to chalcidoid wasps (Monodontomerus obscurus), potential parasites of A. manicatum, in Y-maze olfactometer tests. Also, when exposed at sites where A. manicatum occurs in natural populations, brood cells smeared with trichome secretions were less affected by wasp (Melittobia acasta) parasitism than those without trichome secretions. On the other hand, trichome secretions did not prevent the growth of mold on brood cells, and larval mortality due to microbial decay was almost non-existent even when brood cells were exposed to rainfall. We conclude that the use of plant trichome secretion for brood cell construction has more likely evolved to create enemy-free space in response to chalcidoid wasp parasitism. Parasitoids are likely an underestimated cause of the diversification of cell construction materials and adaptive radiation in megachilid bees.